Prognostic Impact of Intensified Maintenance Therapy on Children With Advanced Lymphoblastic Lymphoma: A Report From the Japanese Pediatric Leukemia/Lymphoma Study Group ALB‐NHL03 Study. Issue 3 (19th November 2015) - Sunami, Shosuke; Sekimizu, Masahiro; Takimoto, Tetsuya; Mori, Tetsuya; Mitsui, Tetsuo; Fukano, Reiji; Saito, Akiko Moriya; Watanabe, Tomoyuki; Ohshima, Koichi; Fujimoto, Junichiro; Nakazawa, Atsuko; Kobayashi, Ryoji; et al.
Abstract : Background: Childhood advanced lymphoblastic lymphoma (LBL) has a favorable outcome with an event‐free survival (EFS) rate of over 80% in response to treatment strategies for acute lymphoblastic leukemia (ALL). However, no progress has been made in this outcome over the past 10 years. Procedure: We conducted the first nationwide prospective study of childhood advanced LBL to assess the efficacy and safety of ALL‐directed therapy with an intensified maintenance phase. We omitted local radiotherapy including prophylactic cranial radiotherapy except for patients with initial central nervous system disease. The total duration of the treatment was 24 months. Results: For the 136 patients analyzed in this study, 5‐year overall survival (OS) was 82.9% and 5‐year EFS was 77.9%. Thirty events were observed and 14 occurred before the initiation of intensified maintenance phase. Of 14 events, nine were observed as mediastinal enlargement. There was no significant difference in outcome when stratified according to gender or by immunophenotype. The 5‐year EFS according to clinical stage in patients with T‐cell LBL (T‐LBL) was 70.6% for stage III and 88.9% for stage IV ( P = 0.037). Conclusions: Our first nationwide study provided about 80% cure rate with only one case of toxic death in childhood advanced LBL. However, our intensified maintenance therapy could not improve the survival outcome. There was a trend of better EFS in Japanese patients with T‐LBL stage IV than T‐LBL stage III.